2020
DOI: 10.1039/c9lc01030k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress induced astaxanthin accumulation of H. pluvialis on a chip

Abstract: A Haematococcus pluvialis culture platform capable of sorting motile vegetative stages cells and culturing the selected cells under controlled mechanical stress to screen the condition that maximizes the astaxanthin accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…It has been confirmed that endogenously generated reactive oxygen species (ROS) induced by stress conditions are essential for the transformation of H. pluvialis from the macrozooid (green) stage to the hematocyst (red) stage, which leads to astaxanthin accumulation. Thus, H. pluvialis cultures have been subjected to various stresses, such as abiotic and chemical treatments, in efforts to increase astaxanthin biosynthesis up to commercially viable levels. For example, it was found that electrical stimulation improved the growth of H.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that endogenously generated reactive oxygen species (ROS) induced by stress conditions are essential for the transformation of H. pluvialis from the macrozooid (green) stage to the hematocyst (red) stage, which leads to astaxanthin accumulation. Thus, H. pluvialis cultures have been subjected to various stresses, such as abiotic and chemical treatments, in efforts to increase astaxanthin biosynthesis up to commercially viable levels. For example, it was found that electrical stimulation improved the growth of H.…”
Section: Introductionmentioning
confidence: 99%
“…As tendências relacionadas ao consumo de alimentos naturais para melhorar a saúde humana estão mudando e o interes-se por esses produtos alimentares estão aumentando. Portanto, a indústria de alimentos está desenvolvendo novos produtos alimentícios enriquecidos com ingredientes funcionais que podem fornecer benefícios à saúde, além dos nutrientes tradicionais (Yao et al, 2020). Dessa forma, as microalgas podem ser de grande relevância, visto que são uma fonte importante de nutrientes funcionais com várias aplicações biotecnológicas em potencial comprovadas (Michalak;Chojnacka, 2015).…”
Section: Potencial Biotecnológico Da Haematococcus Pluvialisunclassified
“…Astaxanthin biomolecules accumulate inside neutral lipid bodies forming ester bonds with long-chain fatty acids, enabled by closely interconnected metabolic networks of lipogenesis and carotenogenesis [6]. To improve the astaxanthin productivity of photosynthetic H. pluvialis cultures, various stress-inducing strategies, such as nitrogen starvation [7], strong light irradiance [8], high salinity [9], high temperature [10], mechanical stress [11], electrical treatment [12], and aminoclay nanoparticle addition [2] have been applied. However, these approaches are time-consuming, require high energy input and large amounts of chemicals; additionally, they may substantially inhibit cell growth.…”
Section: Introductionmentioning
confidence: 99%